Urea and Iron (II) Impurities: Impact on Sulphamic Acid Single Crystal Properties - S. Rajyalakshmi; K. Sujatha; T.V. Rambabu (Revista Electronica de Veterinaria, 2024)
Characterization and Optical Properties of Doped Sulphamic Acid Single Crystals. Sulphamic acid (SA) single crystals doped with iron (Fe2+) and urea were grown using conventional methods. X-ray diffraction (XRD) analysis confirmed the orthorhombic structure of the doped crystals. UV-Visible spectroscopy revealed the optical transmittance of electromagnetic radiation in the doped crystals. The results showed that the efficiency of the doped crystals followed the order: SA (undoped) > Fe:SA (iron-doped) > Urea:SA (urea-doped). This study highlights the potential of doping sulphamic acid single crystals with iron and urea to modify their optical properties.